An Update on Civilian Spinal Gunshot Wounds. Issue 7 (1st April 2015) - Bumpass, David B.; Buchowski, Jacob M.; Park, Andrew; Gray, Benjamin L.; Agarwal, Rashmi; Baty, Jack; Zebala, Lukas P.; Riew, K. Daniel; Santiago, Paul; Ray, Wilson Z.; Wright, Neill M.
<x xml:space="preserve">Abstract</x> Study Design. Retrospective analysis of inpatient and outpatient data from a single academic trauma center. Objective. To test the effectiveness of a conservative treatment algorithm for civilian spinal gunshot wounds (CSGSWs) by comprehensively evaluating neurological status and recovery, fracture type, concomitant injuries, indications for surgery, and complications. Summary of Background Data. Few large studies exist to guide treatment of CSGSWs, and none have been published in nearly 20 years. Methods. A search of International Classification of Diseases, Ninth Revision (ICD-9) codes was performed for all hospital patients treated from 2003 to 2011 by either neurosurgery or orthopedic surgery to identify 159 consecutive patients who sustained CSGSWs. Mean follow-up was 13.6 months. American Spinal Injury Association grading was used to assess neurological injury. Results. Fifty percent of patients had neurological deficits from CSGSW. Complete spinal injury was the most common injury grade; thoracic injuries had the most risk of complete injury (P < 0.001). Nearly 80% of patients had concomitant injuries to other organs. Operative treatment was more likely in patients with severe neurological injuries (P = 0.008) but was not associated with improved neurological outcomes (P = 1.00). Nonoperative treatment did not lead to any cases of late spinal instability or neurological deterioration. Overall, 31% of patients had an improvement of at least 1 American Spinal Injury Association grade by final follow-up. Nearly half of patients experienced at least 1 GSW-related complication; risk of complications was associated with neurological injury grade (P < 0.001) and operative treatment (P = 0.04). Conclusion. The vast majority of CSGSWs should be managed nonoperatively, regardless of neurological grade or number of spinal columns injured. Indications for surgery include spinal infection and persistent cerebrospinal fluid leaks. Level of Evidence: 3